Analisis Pengaruh Konsumsi Energi Non Renewable Resources Terhadap Pertumbuhan Ekonomi di Indonesia Pada Periode 1980-2014 - Akandy, Putri Ayu (Jurnal Ilmiah Mahasiswa FEB, 2017)
This study attempts to examine the influence of energy consumption non renewable resources on economic growth in indonesia.The use writers economic growth as dependent variable and makes variable energy consumption as the independent variable.An approach that used in this research was using data analysis time series, the quantitative approach descriptive and choose method vector error corection model (vecm) to know the influence of independent variable dependent variable in the short term and long term using data in 1980 until 2014.Based on the research done and discussion has been done so can be drawn the conclusion that is the energy consumption on economic growth in indonesia in the period 1980-2014. Test kointegrasi shows that the long term influence of energy consumption on economic growth viewed from the trace statistic larger than critical value and value max-eigen statistic also larger than critical value.To test estimation vecm shows that the influence short and long term of energy consumption on economic growth viewed from the t-statistik larger than the t-tabel.Then the impulse response function at the beginning of a period of consumption energ on economic growth give a positive influence, but dipertengahan period exert negative until late period.This could negative by request and pitches decreasing because depleted the availability of renewable energy not in indonesia.Keywords: Â Â Energy Consumption dan Economic Growth